Evaluation of microplastics ingested by sea cucumber stichopus horrens in Pulau Pangkor, Perak, Malaysia - Muhammad Husin, Miftahul Jannah; Mazlan, Nurzafirah; Shalom, Jemimah; Saud, Safaa Najah; Abdullah Sani, Muhamad Shirwan (Springer Nature, 2021)
The widespread presence of microplastics has caused significant concerns on their potential effects on marine ecosystems. Microplastics are classified as plastic products of less than 5 mm in size and are known to be one of the most dangerous aquatic debris to marine species. Sea cucumbers are deposit feeders living in sediment regions and benthic zone that may collect microplastics in low-energy environments. This research aims to evaluate the types of microplastic isolated from the intestine of Stichopus horrens in Malaysia. This species is selected because it is mainly found in this island. Pulau Pangkor is one of the leading tourism destinations on the small islands is facing increasing numbers of tourists and development and it is useful for sustainable study. A total of 20 S. horrens samples collected from Pulau Pangkor, Malaysia were dissected, and their intestines were collected for digestion. Microplastics were extracted using NaOH and filtered using filter paper.Microplastic identification was conducted on the based of the physical characteristics (colour, shape, size) and chemical characterisation was evaluated using FTIR for polymer functional groups. A total of 1446 unit of microplastics were found in S. horrens. Among various types and colours, fibre (90%) and black (59%) were dominant amongst the various particles identified. The majority ofmicroplastics sizes were 0.51 μm and 1–2 μm. Two polymer materials were identified, namely polyethylene and poly(methyl methacrylate). As a conclusion, the findings of the study will serve as primary data for pollution indicators in respective islands. The microplastics could impact the immune system and upset gut’s balance of human.